Endovascular Reconstruction for Total Aorto–Iliac Occlusion. (August 2022) - Piffaretti, Gabriele; Fargion, Aaron Thomas; Dorigo, Walter; Pulli, Raffaele; Ferri, Michelangelo; Antonello, Michele; Bellosta, Raffaello; Veraldi, Gianfranco; Benedetto, Filippo; Gargiulo, Mauro; Pratesi, Carlo
Objectives: To analyze outcomes following endovascular treatment of total occlusion of the infrarenal aorta and aorto–iliac bifurcation in a multicenter Italian registry. Methods: It is a multicenter, retrospective, observational cohort study. From January 2015 to December 2018, 1306 endovascular interventions for aorto–iliac occlusive disease were recorded in the vascular registry. For this analysis, only patients treated for total occlusion of the infrarenal aorta and aorto–iliac bifurcation were included. Early (<30 days) primary outcomes of interest were technical success and mortality. Late major outcomes were primary and secondary patency and freedom from conversion to open aortic surgery. Results: A total of 54 (4.1%) patients met the inclusion criteria. Total percutaneous revascularization was possible in 41 (75.9%) patients and hybrid (endo plus open) intervention in 13 (24.1%) patients. The kissing-stent-graft technique was used in 45 (83.3%) cases, covered endovascular reconstruction of the aortic bifurcation (CERAB) in 5 (9.2%), and a unibody endograft deployed in 4 (7.4%). Technical success was 98.1% (n = 53). There were no episodes of intraoperative or perioperative vessel rupture. Conversion to open surgery was not necessary, and there were no in-hospital deaths. The median patient follow-up time was 16 months (interquartrile range [IQR], 6-27). The estimated primary patency rate was 95.8% ± 0.03 (95% confidence interval [CI]: 85.5-98.9) at 1 year, 91.4% ± 0.05 (95% CI: 76.2-97.2) at 2 years, and 85 ± 0.08 (95% CI: 64.5-94.6) at 3 years. Cox regression analysis demonstrated that sex (hazard ratio [HR]: 0.96; 95% CI: 0.15-6.23, p = 0.963), extent of the occlusion (HR: 0.28; 95% CI: 0.05-1.46, p = 0.130), calcium score (HR: 1.88; 95% CI: 0.31-11.27, p = 0.490), or type of endovascular reconstruction (HR: 0.80; 95% CI: 0.13-5.15, p = 0.804) did not affect primary patency. Secondary patency was 95.5% ± 0.04 (95% CI: 78.4-99.2) at 3 years. No patients required late conversion to open surgical bypass. Conclusions: Endovascular reconstruction for total occlusion of the infrarenal aorta and aorto–iliac bifurcation was successful using a combination of percutaneous and hybrid revascularization techniques. Estimated patency rates at 3 years of follow-up are promising and are unaffected by the extent of occlusion or type of revascularization.